Media Reports as a Source of Information for Creating Advisory Bibliographic Resources for the Development of Scientific Worldview - A. V. Yuklyaevskaya (Библиосфера)
Dissemination and updating advisory bibliographic resources on scientific knowledge, promoting a deep understanding of scientific problems by the public are becoming most important tasks of the library. The purpose of the article is to show the possibility of using messages from the mass media as one of the sources for creating such bibliographic resources. The author presents the results of monitoring 146 Russian media using the Medialogy database (69 federal, 77 regional), conducted in March – April 2023. These analyzed media reports have allowed the identification of objects (organizations, persons, project names) involved in the communication of science and society. As a result of the study, a list of 334 messages served as the most notable informational occasions has been formed. These messages can be the objects of bibliographic description, as well as factual information for creation advisory bibliographic resources (lists, reviews, newsletters, digests, databases, guidebooks) aimed at increasing public awareness of the development of science and disseminating scientific literacy.